Attosecond photoionization dynamics around Ar Cooper minimum. Issue 7 (January 2020) - Lejman, M; Alexandridi, C; Turconi, M; Barreau, L; Platzer, D; Borot, A; Hergott, J-F; Tcherbakoff, O; Salières, P
Synopsis: Photoionization time delays between the 3s and 3p subshells of argon have been measured over a large energy range (35-70eV) covering the Cooper minima in both subshells, providing stringent tests for interchannel correlation theories.